Deterministic inventory model for items with time varying demand, Weidull distribution deterioration and shortages - Wu, K.-S. (Yugoslav Journal of Operations Research, 2016)
In this paper, an EOQ inventory model is depleted not only by time varying demand but also by Weibull distribution deterioration, in which the inventory is permitted to start with shortages and end without shortages. A theory is developed to obtain the optimal solution of the problem